Professional competence of the future primary school teacher in the conditions of educational renewal - Сыздыкбаева, Айгуль; Турланкызы, Айгүл (Pedagogy and Psychology, 2021)
The article examines the process of developing the professional competence of a future primary school teacher in the context of education renewal. The purpose of the study: theoretical substantiation and determination of the level of development of professional competence of the future primary school teacher on the example of national and regional universities of the country. The concept of "professional competence" is analyzed, the structure of professional competence of a teacher is determined. Based on the analysis of foreign studies in the field of vocational training, the relevant competencies for the future primary school teacher are highlighted: innovative thinking, digital literacy, global citizenship, competence in pedagogical assessment, regulatory competence, teamwork and leadership, self-care skills and others. The levels of development of professional competence of the future primary school teacher in the conditions of education renewal are substantiated: intuitive, reproductive, creative. The program of diagnostics of the development of professional competence of the future primary school teacher is presented. The diagnostic results stated the low level of development of the professional competence of the future primary school teacher in a regional university, the reasons were analyzed and recommendations were developed for the development of the professional competence of the future primary school teacher in the conditions of professional training.